"American Defenders Against an Illegal Invasion": Dual Racialization Processes in Collective Identity Formation. (November 2022) - Hummel, Joshua R.
This paper considers how the anti-immigrant organization Americans for Legal Immigration PAC (ALIPAC) uses discourse about immigrants and immigration to construct and maintain its collective identity. Although previous approaches to collective identity within organizations primarily center the organizations themselves, studies concerned with anti-immigrant discourse instead emphasize how the organizations that use such discourse racialize members of non-white (especially Latinx) groups as "illegal" residents of the United States who threaten the safety and economic well-being of Americans. Drawing from these two literatures to consider how anti-immigrant organizations construct collective identity, this study investigates how ALIPAC uses presentations its opposition and its membership together to shape the collective identity associated with the organization itself. Using a content analysis, 153 documents released by ALIPAC during 2005 and 2018, the study finds that ALIPAC uses a dual racialization process to racialize immigrants as criminal outsiders who, with assistance from political elites, have overwhelmed the United States and white Americans as victims of these criminal outsiders. From this dual racialization, ALIPAC identifies itself as a defender of American citizens against an immigrant invasion. These results illustrate how racialization and collective identity construction are relational processes understood through a group's presentations of itself and its opposition.